3D GPR investigation of pavement using 1 GHz and 2 GHz horn type antenna – comparison of the results - GRINČ, Michal (Contributions to Geophysics and Geodesy, 2015)
Today, non-invasive, simple, safe, time efficient and traffic flow non-disturbing methods of the pavement diagnostics are requested. From this point of view a very convenient method seems to be the GPR investigation. The trial GPR survey of the Žilina airport was carried out in order to investigate the pavement of the runway. A testing field is placed where the geological drill hole has been drilled out. The GPR survey was performed in 3D geometry, hence in x and y directions. Two horn type antennas with central frequencies of 1 GHz and 2 GHz were used on the test field in order to verify thicknesses of pavement construction layers Here, the results of both 3D measurements are compared to each other However the investigation confirms two subhorizontal construction layers of the runway pavement, the results obtained in y-direction slightly differ at someareas. These errors are situated mainly in the areas where the linear cracks are found. On the other hand, results in x-directions are within standard error.